PENINGKATAN KUALITAS PENDIDIKAN DAN KETERAMPILAN DI PKBM BUDI ILMU KECAMATAN BALEN - Nurdianingsih, Fitri; Rohmah, Ima Isnaini Taufiqur; Rozak , Refi Ranto; Wahyuni , Sri; Izzatisselim, Zilvia Nur (Penerbit LPPM- STKIP PGRI Bangkalan, 2025)
This community service activity aims to enhance the quality of education and skills at PKBM Budi Ilmu in Balen District through training programs in literacy, numeracy, educational technology, and vocational skills. The implementation methods included needs assessment surveys, training sessions, workshops, and evaluations. The results indicate significant improvements in institutional management, learners’ literacy and numeracy skills, the use of technology in learning, and entrepreneurial competencies. Furthermore, the program received positive responses from the community. It is concluded that ongoing support from various stakeholders is essential to sustain and expand the impact of this program.